Novas práticas de comunicação e consumo: os processos transmidiáticos da Capricho no plano da recepção e interatividade das adolescentes - Maia, Roberta Scorcio (2012)
Several phenomena involves interactivity and transmidiality processes in face of sociocultural context , articulated by media consumption, particularly in light of the teenagers culture´s generational transit, through those involving communication and consumption, both integral parts of the new contemporary communication's dynamics. In this study, we tried to deepen the discussion of those issues through reception angle, analyzing them from the point of view of the teenage girls universe, as active and prosumer receptors that, through the central role played by the cross-platform media and supported by new technologies, propose new forms of participations, conferred by borderline communication actions and by been interwoven to the new communication s practices within the production strategies of Capricho magazine, can be understood from the virtual the online platform, to presential, represented by NoCapricho event. Those phenomena consolidate the productive power of the intersection of reception and production s axes, which coupled with mediatic culture, come to define the new communication and consumption practices.